Activation of LXR Nuclear Receptors Impairs the Anti-Inflammatory Gene and Functional Profile of M-CSF-Dependent Human Monocyte-Derived Macrophages - González de la Aleja, Arturo; Herrero, Cristina; Torres-Torresano, Mónica; de la Rosa, Juan Vladimir; Alonso, Bárbara; Capa-Sardón, Enrique; Muller, Ittai B.; Jansen, Gerrit; Puig-Kröger, Amaya; Vega, Miguel A.; Castrillo, Antonio; Corbí, Ángel L. (Frontiers in Immunology, 2022)
Liver X Receptors (LXR) control cholesterol metabolism and exert anti-inflammatory actions but their contribution to human macrophage polarization remains unclear. The LXR pathway is enriched in pro-inflammatory macrophages from rheumatoid arthritis as well as in tumors-associated macrophages from human tumors. We now report that LXR activation inhibits the anti-inflammatory gene and functional profile of M-CSF-dependent human macrophages, and prompts the acquisition of a pro-inflammatory gene signature, with both effects being blocked by an LXR inverse agonist. Mechanistically, the LXR-stimulated macrophage polarization shift correlates with diminished expression of MAFB and MAF, which govern the macrophage anti-inflammatory profile, and with enhanced release of activin A. Indeed, LXR activation impaired macrophage polarization in response to tumor-derived ascitic fluids, as well as the expression of MAF- and MAFB-dependent genes. Our results demonstrate that LXR activation limits the anti-inflammatory human macrophage polarization and prompts the acquisition of an inflammatory transcriptional and functional profile.